ISSUES ON ENFORCEABILITY OF FINAL DECISIONS OF EUROPEAN UNION INTELLECTUAL PROPERTY OFFICE REGARDING EUROPEAN TRADEMARKS ON FIXING THE AMOUNT OF COST IN ROMANIA - Sorin Eduard PAVEL (Challenges of the Knowledge Society)
The purpose of this paper is to analyse the enforceability in Romania of final decisions fixing the amount of costs related to European trademarks, issued by European Union Intellectual Property Office. According to art 110 (1) and (2) of EU Regulation 2017/10011 , such decisions are titles enforceable in any Member State and enforcement proceedings are governed by applicable national civil law of the Member State in territory of which the enforcement is carried out. Apparently, the enforcement of these decisions in Member States should be a formal procedure devoid of issues. Things may be complex having in view that each Member State is compelled by the art 110 (2) of the EU Regulation 2017/1001, to designate a national authority responsible with the verification of the authenticity of respective decisions. Precisely, what happens when a Member State "forgot" to designate such national authority? Can enforcement proceedings regarding these decisions in respective Member State, be effective? Romania does not designate the national authority prescribed under art. 110 (2) of EU Regulation 2017/1001, fact that generates, at least from theoretical perspective, issues on the enforcement of this kind of decisions. In a nutshell, if no such national authority has been designated, the procedure on verification of authenticity of these decisions cannot be fulfilled, meaning that enforcement proceedings may be deemed as failing to comply with the national law.